PENGARUH THIN CAPITALIZATION, LEVERAGE, DAN LIKUIDITAS TERHADAP TAX AVOIDANCE - Swissia, Pebrina; Irawati, Anik; Khoiriyah, Yaumil (Jurnal Riset Terapan Akuntansi, 2024)
This research was to determine the effects of Thin capitalization, Leverage, and Liquidity on Tax Avoidance in Non-Cyclical Consumer Companies in Indonesia during the period 2020 to 2021. The method used was quantitative descriptive using SPSS ver 26. The population was non-cyclical consumer companies registered inIndonesian Stock Exchange (BEI) for the 2020-2022 period. Sample selection using purposive sampling resulted in 62 companies as research samples. The research results showed that Thin Capitalization has a significant effect on Tax Avoidance. Meanwhile, Leverage and Liquidity have no significant effect on Tax Avoidance.Keywords: Thin Capitalization, Leverage, Liquidity, Tac Avoidance